Speed tracking and synchronization of multiple motors using ring coupling control and adaptive sliding mode control. (September 2015) - Li, Le-Bao; Sun, Ling-Ling; Zhang, Sheng-Zhou; Yang, Qing-Quan
Abstract: A new control approach for speed tracking and synchronization of multiple motors is developed, by incorporating an adaptive sliding mode control (ASMC) technique into a ring coupling synchronization control structure. This control approach can stabilize speed tracking of each motor and synchronize its motion with other motors׳ motion so that speed tracking errors and synchronization errors converge to zero. Moreover, an adaptive law is exploited to estimate the unknown bound of uncertainty, which is obtained in the sense of Lyapunov stability theorem to minimize the control effort and attenuate chattering. Performance comparisons with parallel control, relative coupling control and conventional PI control are investigated on a four-motor synchronization control system. Extensive simulation results show the effectiveness of the proposed control scheme. Highlights: A new control approach for speed tracking and synchronization of multi-motor is developed. An adaptive law is exploited to estimate the unknown bound of uncertainty. The approach makes speed tracking errors and synchronization errors converge to 0. The proposed control scheme is robustness to parameter variations and disturbances. Performance comparisons with other methods are also investigated.